CCL2 accelerates microglia-mediated Abeta oligomer formation and progression of neurocognitive dysfunction. - Tomomi Kiyota; Masaru Yamamoto; Huangui Xiong; Mary P Lambert; William L Klein; Howard E Gendelman; Richard M Ransohoff; Tsuneya Ikezu (PLoS ONE)
Background The linkages between neuroinflammation and Alzheimer's disease (AD) pathogenesis are well established. What is not, however, is how specific immune pathways and proteins affect the disease. To this end, we previously demonstrated that transgenic over-expression of CCL2 enhanced microgliosis and induced diffuse amyloid plaque deposition in Tg2576 mice. This rodent model of AD expresses a Swedish beta-amyloid (Abeta) precursor protein mutant. Methodology/principal findings We now report that CCL2 transgene expression accelerates deficits in spatial and working memory and hippocampal synaptic transmission in beta-amyloid precursor protein (APP) mice as early as 2-3 months of age. This is followed by increased numbers of microglia that are seen surrounding Abeta oligomers. CCL2 does not suppress Abeta degradation. Rather, CCL2 and tumor necrosis factor-alpha directly facilitated Abeta uptake, intracellular Abeta oligomerization, and protein secretion. Conclusions/significance We posit that CCL2 facilitates Abeta oligomer formation in microglia and propose that such events accelerate memory dysfunction by affecting Abeta seeding in the brain.